Removal of Lead Ions from Aqueous Solution using Zirconium Dioxide Nanoparticles - Nguyen, Tan Tai (Asian Journal of Chemistry, 2023)
This study demonstrated the feasibility of using zirconium dioxide nanoparticles (ZrO2 NPs) synthesixed using a hydrothermal technique for the removal of lead in aqueous solution. The physico-chemical characterization illustrated that the synthesized ZrO2 NPs have a non-uniform shape with an average size of 15 nm, surface area of 41.56 m2 g-1 and adsorption pore width of 3.06 nm. These findings revealed the potential use of ZrO2 NPs for chelating lead ions. The maximum lead adsorption capacity of ZrO2 NPs was obtained around 4.12 mg g-1 at adsorption conditions i.e., stirring speed of 200 rpm and contact time of 120 min. Thus, this method provides a number of advantages, including an efficient and cost-effective method for the removal of lead using ZrO2 NPs.